Research of Bipolar HVDC Transmission Lines Based on Traveling Wave Differential Protection - Baina He; Yunwei Zhao; Hengxu Ha (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The principle of the traveling wave based differential protection for bipolar HVDC transmission lines is proposed in the paper. Unlike the traditional current differential protection, the quantity of current is replaced by the quantity of the traveling wave for comparison. The traveling wave at the remote end is transferred to the local end for comparison to the local traveling wave. For the bipolar DC transmission lines, the polar-mode (aerial mode) traveling waves are employed to establish the discriminative criterion. The ground-mode traveling waves are utilized for faulty line detector for bipolar operation modes. The entire protection scheme is simulated in PSCAD/EMTDC associated with the standard ±500kV HVDC transmission system. The simulation results show that the new protection has the advantages of higher sensitivity, reliability and security. The fault resistance can be coverd by the traveling wave based differential protection reaches to 500 Ohm.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3700